The Comparison of Hearing Capabilities and Blood Pressure with Reference to Noise Pollution in Rural/Urban Areas of District Hyderabad - Shah, Tazeen; Warsi, Jamshed; Mahar, Benazir; Ansari, Shafaq (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To compare the noise pollution and blood pressure in urban and or rural areas of Hyderabad, Sindh, Pakistan. METHODOLOGY: A comparative cross sectional study was conducted from April 2018 to September 2018. The sample size was randomly selected 201 young adults of either gender between 18 to 25 years of age. RESULTS: The hearing frequency in rural female (29.34Hz±8.04) was significantly (p<0.05) less than the urban female (49.09Hz±7.76). Similarly, the hearing frequency in rural male (24.72± 7.0) was also significantly (p= <0.05) less than that of urban group (40.56Hz±7.6). The systolic and pulse pressure (106.2mmHg±4.35and 38.88mmHg±4.8) was recorded significantly (p=<0.05) lower in rural than Urban female (114.2mmHg±6.03and45.76±4.8). Moreover, the systolic and pulse pressure (108.3mmHg±5.40 and 42.4mmHg±4.71) was significantly (p=<0.05) lower in rural than urban males (114.2mmHg±6.00 and 47.33mmHg±5.00mmHg) respectively. CONCLUSION: The study concludes that noise pollution has potent impact on hearing capabilities and blood pressure in urban areas of district Hyderabad, Sindh, Pakistan